Freud y la quietud de los que fueron: una aproximación al concepto de pulsión de muerte desde la poesía de José Asunción Silva (2019)
Like Sigmund Freud, founder of psychoanalysis, José Asunción Silva delved into what deepest recesses of humanity determined to expose without concessions what many had insisted on ignoring, armed with an uncommon lucidity and a refined aesthetic sense that gave his words great forcefulness, especially when spoke of death, a concern shared with the father of abyssal psychology, who always praised the faculties of artists, a kind of bridge between the common man and the forces that govern his life, an attribute that he used to study life emotional, composed among other elements of the aspirations that move the apparatus psychic to act and that tend to be abstracted from the consideration of the individual.